2003
DOI: 10.2307/3868092
|View full text |Cite
|
Sign up to set email alerts
|

Down by the Riverside: Urban Riparian Ecology

Abstract: Riparian areas are hotspots of interactions between plants, soil, water, microbes, and people. While urban land use change has been shown to have dramatic effects on watershed hydrology, there has been surpris ingly little analysis of its effects on riparian areas. Here we examine the ecology of urban riparian zones, focusing on work done in the Baltimore Ecosystem Study, a component of the US National Science Foundation's Long Term Ecological Research network. Research in the Baltimore study has addressed how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
204
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(213 citation statements)
references
References 0 publications
6
204
1
2
Order By: Relevance
“…The findings of this study begin to address questions regarding how urbanization affects the function of riparian zones, an understudied area in the urban ecology literature (Groffman et al 2003). This study demonstrates the importance of preserving near-stream remnant riparian areas in cities to maintain patterns of carbon and nutrient fluxes in urban streams.…”
Section: Discussionmentioning
confidence: 89%
“…The findings of this study begin to address questions regarding how urbanization affects the function of riparian zones, an understudied area in the urban ecology literature (Groffman et al 2003). This study demonstrates the importance of preserving near-stream remnant riparian areas in cities to maintain patterns of carbon and nutrient fluxes in urban streams.…”
Section: Discussionmentioning
confidence: 89%
“…Despite reduced spatial variation of nutrient concentrations in this urban watershed (i.e., Fig. 7), high spatial variation in drivers of nutrient limitation such as riparian vegetation (Groffman et al 2003) may directly alter biofilm nutrient limitation status at nearby NDS sites.…”
Section: Hydrological Modificationmentioning
confidence: 99%
“…Such ''hydrological droughts'' and lowering of the water Table 1. Impacts of urbanization on stream hydrology and geomorphology (modified from Baer & Pringle, 2000) Changes to stream hydrology Increase in frequency and magnitude of severe floods (Groffman et al, 2003). Williams (1999) observed that many urban streams in semi-arid areas such as Adelaide, South Australia were temporary and their flow regimes had been altered through use as conduits for waste-water, being fed by runoff from domestic use (e.g., watering gardens), or carrying flashy flows from the rapid runoff from impervious catchments.…”
Section: Impacts Of Urbanization On Hydrology and Geomorphologymentioning
confidence: 99%